Ovarian Torsion in the Third Trimester of Pregnancy Leading to Iatrogenic Preterm Delivery - Evangelia Vlachodimitropoulou Koumoutsea; Manish Gupta; Antony Hollingworth; Anwen Gorry (Hindawi Limited, 2016)
Ovarian torsion in the third trimester of pregnancy leading to a midline laparotomy and caesarean section for the delivery of a preterm baby is an uncommon event. As the woman is likely to present with nonspecific symptoms of lower abdominal pain, nausea, and vomiting, ovarian torsion can often be misdiagnosed as appendicitis or preterm labour. Treatment and the opportunity to preserve the tube and ovary may consequently be delayed. We report the case of a multiparous woman who had undergone two previous caesarean sections at term, presenting at 35 weeks of gestation with a presumptive diagnosis of acute appendicitis. Ultrasonography described a cystic lesion 6 × 3 cm in the right adnexa, potentially a degenerating fibroid or a torted right ovary. MRI of the pelvis was unable to provide further clarity. The patient was managed by midline laparotomy and simultaneous detorsion of the ovarian pedicle and ovarian cystectomy together with caesarean section of a preterm infant. This report describes that prompt recognition and ensuring intraoperative access can achieve a successful maternal and fetal outcome in this rare and difficult scenario. Furthermore, we would like to emphasise that the risk for a pregnant woman and her newborn could be reduced by earlier diagnosis and management of ovarian masses (Krishnan et al., 2011).